Lutein/β-carotene ratio in extra virgin olive oil: An easy and rapid quantification method by Raman spectroscopy. (15th March 2023) - Portarena, Silvia; Anselmi, Chiara; Leonardi, Luca; Proietti, Simona; Bizzarri, Anna Rita; Brugnoli, Enrico; Baldacchini, Chiara
Highlights: Raman spectroscopy was used to quantify lutein/β-carotene (l/β) ratios in olive oil. Carotenoid CC stretching mode band (ν1) position depended upon l/β ratio. Two-component fit allowed calibration of relative l/β content. Abstract: Carotenoids play an important role in the stability, freshness, and nutritional value of extra-virgin olive oil (EVOO). However, the carotenoid content in EVOO changes over time as a function of olive ripening and degrading events. A reliable quality marker is the ratio between the two most abundant carotenoids, namely lutein and β-carotene, since the second degrades more rapidly. Thus, to obtain a fast quantification of the lutein/β-carotene ratio in olive oil could deserve a certain interest. Resonant Raman spectroscopy is a rapid and non-destructive technique, widely applied for food chemical characterization. In this work, using high-performance liquid chromatography and UV–vis absorption spectroscopy as calibration techniques, we present a reliable method to assess the lutein/β-carotene ratio in EVOO using a single Raman spectrum. The novel approach deserves several methodological and applicative interests, since it would allow rapid, on-site screening of EVOO quality and authenticity, especially if implemented as a portable system.